An Overview of Big Data for Growth in SMEs - VAYVAY, ÖZALP (ELSEVIER SCIENCE BV, 2016)
Potentials and promises of Big Data are significant for SMEs. Big Data can nurture alliance in SMEs by creating real-time solutions to challenges in every industry. This can be achieved by utilizing the openness for decision-making. SMEs are specifically selected within context for two main reasons: a) A small change in SMEs can have larger macro level effect due to their overall position in the economy; b) They have the advantage and flexibility for quicker adaptation to changes towards efficiency. The Big Data context, however, still have significant contentious issues as; storage, capabilities of the companies in terms of processing and generating sensible information from it, and last but not least, security and privacy. This article is aimed to propose grounds for future Big Data research for SMEs by examining main potentials and threats that have to be addressed. Finally, we recommend potential practices that will help SMEs and researchers for capturing the full potential of Big Data. (C) 2016 Published by Elsevier Ltd.
Keywords: Big Data; SME; Growth; CHALLENGES; MANAGEMENT